The Relationship between Extent of Internationalization and Firm Performance (Taiwan 1992–2017). (12th June 2021) - Wei, Shih-Yung; Lin, Li-Wei
Abstract : The purpose of this study was to discuss the impact of the extent of internationalization on firm performance measured for firms with a high Tobin's Q (firms with good operating performance), a median Tobin's Q (firms with average operating performance), and a low Tobin's Q (firms with poor operating performance). In addition to discussion on the impact of internationalization on firm performance, this study also discussed the impact of corporate proprietary assets (using assets, R&D, marketing, and management-related variables as moderating variables) and control variables (scale of company, debt-asset ratio, firm age, board structure, and proportion of pledged shares by directors) on firm performance. The research results showed that there is an S-shaped relationship between extent of internationalization and firm performance. However, further discussion found that there is an S-shaped relationship between extent of internationalization and performance for firms with a high Tobin's Q but a slight decline in the middle of the S-shaped curve, as well as a general linear negative correlation between extent of internationalization and performance for firms with a median Tobin's Q and an inverted U-shaped correlation between extent of internationalization and performance for firms with a low Tobin's Q.